Abstract 280: Risk Factors in 90day Ischemic Stroke Readmissions - Shlee S. Song (Stroke: Vascular and Interventional Neurology)
Introduction The purpose of this study is to conduct a retrospective Medicare Fee‐For‐Service medical claims analysis to identify risk factors associated with 30‐day and 90‐day readmissions in ischemic stroke patients. Methods The Centers for Medicare and Medicaid Services(CMS) Standard Analytic File(SAF) Limited Data Set(LDS) 100% Inpatient, Outpatient and Denominator files 2017‐2019 and ICD‐10‐CM diagnosis codes were used to identify ischemic stroke. Study Population includes all patients with an ischemic stroke inpatient admission in 2018 and were continuously enrolled with Medicare FFS for 1 year prior to and following their initial 2018 stroke admission. Factors considered in analysis include patient age, sex, geographic region, Medicaid dual eligibility, disability status prior to age 65, comorbidities, admission length of stay, discharge disposition, and hospital characteristics. Comorbidities were identified based on ICD‐10 codes on health claims for the full‐year preceding stroke and up to the index stroke hospitalization. We compared these factors among patients who were readmitted within 90‐days post initial stroke admission to those who were not admitted to identify risk factors for readmission Results Among the 200,058 patients discharged following an ischemic stroke in 2018, 25.9% (n=51,860) had an all‐cause 90‐day readmission. Fewer females and white individuals had a 90‐day readmission (53.5% female and 83.1% white in 90‐day population compared to 54.9% and 82.1% in study population). Discharge disposition of subacute nursing facility (SNF) represents 36.1% of the readmission population compared to 27.8% of the study population and 40.2% of those discharged home, in study population vs 36.0% of the readmission cohort. Characteristics that represent a larger portion of the 90‐day readmission cohort compared to the study population include disabled/ESRD (24.8% vs 20.6%) and dual eligible (26.9% vs 22.4%). Comorbidities with the greatest difference in prevalence between the 90‐day readmit and non‐readmit cohorts are coronary cardiac disease (60.48% prevalence in readmit cohort vs 52.62% in non‐readmit cohort), heart failure (37.85% vs 29.24%, diabetes 48.31% vs 42.08%), atrial fibrillation (40.45% vs 36.67%), and chronic kidney disease (39.82% vs 31.23%). In multivariate regression analysis, the factors independently associated with a greater risk of readmission within 90 days were hypercoagulation (1.359 [95%CI, 1.1274‐1.45]), opiod abuse and dependence (1.353 [95%CI, 1.238‐1.478]), chronic kidney disease (1.347 [95%CI, 1.316‐1.379]), liver disease (1.318 [95% CI, 1.26‐1.378]), and heart failure (1.282 [95%CI, 1.25‐1.315]). Conclusion Patient discharge disposition and comorbidities are driving factors in 90‐day readmissions following an ischemic stroke and differ from 30‐day readmissions. Idenfification of these risk factors will help inform the next phase of analysis to design data driven interventions to work towards reducing a large driver of healthcare cost.